PERAN PEREMPUAN NELAYAN DALAM PEMENUHAN KEBUTUHAN HIDUP KELUARGA DI KELURAHAN BUNGKUTOKO KECAMATAN NAMBO KOTA KENDARI - Sukmawati Abdullah (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the activities undertaken by fisherwomen in support of family life and to examine the role of fisherwomen in fulfilling family life needs. The sample determination was executed by means of the Slovin method. The population of interest comprised 460 fishermen, and the number of respondents amounted to 82. The data were collected using a variety of research methods, including survey techniques, interviews, and documentation guided by a questionnaire. The focal variable of this inquiry pertains to the role of fisherwomen in ensuring the well-being of their families. The data were processed using the method of class interval analysis. The results of the study indicated that the role of fisherwomen in fulfilling the needs of family life is divided into two sectors: the domestic and public sectors. Within the domestic sector, which encompasses activities such as cooking, laundry, housekeeping, childcare, and assistance to spouses, fisherwomen are categorized in the moderate group, comprising 50 individuals or 60.97% of the total respondents. In public roles, which include the social sector (majelis ta'alim, arisan groups, dasawisma and PKK), and the economic sector (Joint Business Groups (KUBE), laborers, and private/public employees), women have a role in the low category, namely 73 people or 89.02% of the total respondents.